2021
DOI: 10.1038/s41598-021-82620-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo measurement of pH and CO2 levels in the uterus of sows through the estrous cycle and after insemination

Abstract: The pH–CO2–HCO3− system is a ubiquitous biological regulator with important functional implications for reproduction. Knowledge of the physiological values of its components is relevant for reproductive biology and the optimization of Assisted Reproductive Technologies (ARTs). However, in situ measurements of these parameters in the uterus are scarce or null. This study describes a non-invasive method for in situ time-lapse recording of pH and CO2 within the uterus of non-anesthetized sows. Animals were at thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
0
4
1
Order By: Relevance
“…We also found that the reproductive fluid pH is significantly higher in the uterus and oviduct of the polyandrous deer mouse ( P. maniculatus ) during estrus compared to its monogamous congener, P. polionotus , but that both species have a more alkaline environment in the uterus than oviduct. This result is surprising given that the opposite has been observed in other studies (López-Albors et al 2021, but see Ng et al 2018). Such alkaline environments have been shown to enhance sperm motility in birds ( Gallus domesticus, Coturnix coturnix, Meleagris gallopavo ; Holm and Wishart 1998) and humans (Saito et al 1996; Zhou et al 2015), and to activate sperm-specific CatSper channels in mice ( Mus musculus ; Kirichok et al 2006) and humans (Lishko et al 2010), thereby inducing sperm hyperactivation (Suarez et al 1993).…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…We also found that the reproductive fluid pH is significantly higher in the uterus and oviduct of the polyandrous deer mouse ( P. maniculatus ) during estrus compared to its monogamous congener, P. polionotus , but that both species have a more alkaline environment in the uterus than oviduct. This result is surprising given that the opposite has been observed in other studies (López-Albors et al 2021, but see Ng et al 2018). Such alkaline environments have been shown to enhance sperm motility in birds ( Gallus domesticus, Coturnix coturnix, Meleagris gallopavo ; Holm and Wishart 1998) and humans (Saito et al 1996; Zhou et al 2015), and to activate sperm-specific CatSper channels in mice ( Mus musculus ; Kirichok et al 2006) and humans (Lishko et al 2010), thereby inducing sperm hyperactivation (Suarez et al 1993).…”
Section: Discussioncontrasting
confidence: 70%
“…Our results demonstrate some important differences in the fluid collected from different regions of the female reproductive tract, however finer-scale changes in more localized areas of the reproductive tract and in response to seminal fluids will further enhance our understanding of how selection has shaped the fertilization environment in Peromyscus . Our understanding of the physiological mechanisms required for mammalian fertilization remain obscure without the ability to measure conditions in vivo in real-time (Ng et al 2018), especially in small animals, but our results suggest that even closely-related species may exhibit striking differences similar in magnitude to differences in highly divergent taxa (López-Albors et al 2021). In other mammals, evidence suggests that uterine fluid near the cervix is more viscous than more proximal regions of the uterus, and oviductal fluid in the ampullary region contains viscous compounds produced from ovulating follicles and peritoneal fluid during estrus (reviewed in Hunter et al 2011).…”
Section: Discussionmentioning
confidence: 90%
“…Carbonic anhydrase 1 is a member of the large family of zinc metalloenzymes that catalyze the reversible hydration of carbon dioxide and plays a pivotal role maintaining acid-base homeostasis [ 18 ] possibly impacting in the endometrium, sperm fertilization capacity, embryo transport, development and implantation [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…To assess vaginal permeability in vitro, simulated vaginal fluid (SPVF) was prepared using the composition reported by Owen and Katz for humans [ 15 ] and adjusted with NaOH to pH 7 [ 16 , 17 ] to simulate conditions in the sow vagina [ 18 , 19 ]. Porcine vaginal tissue was obtained from a local abattoir (Murray Bridge, SA, Australia) at slaughter and transported to the laboratory in SPVF on ice.…”
Section: Methodsmentioning
confidence: 99%